Qualitative assessment of the professional level of teachers (Philology, 2019)
The present study focuses on the competencies that educational specialists need to possess as a combination of knowledge, skills and attitudes as defined in Decree-Law No 12 of the Ministry of Education. They are classified into four main categories – academic, pedagogical, communicative and administrative competencies, and each of these categories includes a number of components and their descriptions. The Decree-Law also includes a scale defining the level of readiness to meet the criteria outlined in the different spheres of professional competence. The purpose of the study is based on the experience and opinion of 251 educational leaders (directors, mentors, senior teachers) from 136 educational institutions across the country and offers the educational specialists an assessment tool that is collaboratively produced by all of them and presents a qualitative description of the different levels of the so defined competencies. The tool could be used both to diagnose the current level of the educational specialists and reveal their own strengths and weaknesses, and to direct them towards their future professional development. The tool also aims to unify the content of the professional language used by educational specialists in the interpretation of the so defined competencies.
Keywords: competencies; educational specialists; rubric; students/children